2002
DOI: 10.1021/jp014229s
|View full text |Cite
|
Sign up to set email alerts
|

A Force Field for Liquid State Simulations on Room Temperature Molten Salts:  1-Ethyl-3-methylimidazolium Tetrachloroaluminate

Abstract: A classical force field for the room temperature molten salt 1-ethyl-3-methylimidazolium tetrachloroaluminate has been developed and successfully tested against experimental data (neutron diffraction, diffusion constants) by molecular dynamics computer simulation corresponding to a temperature of 298 K. The force field parameters for the cation have been derived from the AMBER description for the protonated amino acid histidine, whereas the AlCl4 - parameters have been achieved by parametrization of intramolec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
152
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(167 citation statements)
references
References 17 publications
9
152
3
Order By: Relevance
“…They obtained the radial distribution curves of dimethylimidazolium chloride and hexafluoro- [108] phosphate liquids using neutron diffraction and argued for charge ordering of ions in RTILs resembling what is found in the solid state. Charge ordering has also been discussed in a number of molecular dynamics computer simulation studies on 1-alkyl-3-methylimidazolium-based RTILs in recent few years [47,[142][143][144][149][150][151][152][153][154][155][156][157][158][159]. The radial distribution functions calculated in these papers all have suggested long-range charge ordering, giving support to the idea that RTILs are unique in having more structure ordering than do conventional molecular liquids.…”
Section: Local Structures In Ionic Liquidsmentioning
confidence: 85%
“…They obtained the radial distribution curves of dimethylimidazolium chloride and hexafluoro- [108] phosphate liquids using neutron diffraction and argued for charge ordering of ions in RTILs resembling what is found in the solid state. Charge ordering has also been discussed in a number of molecular dynamics computer simulation studies on 1-alkyl-3-methylimidazolium-based RTILs in recent few years [47,[142][143][144][149][150][151][152][153][154][155][156][157][158][159]. The radial distribution functions calculated in these papers all have suggested long-range charge ordering, giving support to the idea that RTILs are unique in having more structure ordering than do conventional molecular liquids.…”
Section: Local Structures In Ionic Liquidsmentioning
confidence: 85%
“…There have been several molecular dynamics (MD) simulations of ionic liquids based on imidazolium, pyridinium and ammonium cations. These studies modeled bulk properties, such as melting points, 8 diffusion, [8][9][10][11][12] and viscosity. 8,9 Radial distribution functions 8,10,[12][13][14][15][16] and densities have also been calculated.…”
Section: Introductionmentioning
confidence: 99%
“…16 Systematic MD studies of 1-alkyl-3meth-ylimidazolium ionic liquids with several anions have been performed using various classical force fields. 11,17 Three first principles based MD studies on 1,3-dimethylimidazolium chloride have been performed and compared to classical simulations and experimental neutron scattering experiments. [12][13][14] There are differences in the local structures predicted by classical vs first principles based MD.…”
Section: Introductionmentioning
confidence: 99%
“…[13] However, using rigid molecules in a simulation may not be a large approximation as analysis of selected bond stretching, bending and torsional motions has shown that the imidazolium ring is almost rigid. [14] The AlCl 4 -anion has also been shown to be almost rigid. [14] One problem facing groups attempting to develop potentials for the imidazolium based ionic liquids, is a lack of useful experimental data.…”
Section: Force Field Developmentmentioning
confidence: 99%
“…[14] The AlCl 4 -anion has also been shown to be almost rigid. [14] One problem facing groups attempting to develop potentials for the imidazolium based ionic liquids, is a lack of useful experimental data. Parameters have been taken directly from established force fields without adjustment to experimental data (for example, the heat of vaporization), and simulations have therefore necessarily been predictive.…”
Section: Force Field Developmentmentioning
confidence: 99%